Darshane as an Epistemological Ecosystem: Reconstructing Muslim Identity Through the Thought of Badiuzzaman Said Nursi (Lembaga Contrarius Indonesia, 2026)
This article examines the darshane namely study circles inspired by the Risale-i Nur corpus, as a dynamic epistemological ecosystem that cultivates holistic Muslim identity formation in the contemporary world. Drawing on the intellectual legacy of Badiuzzaman Said Nursi (1877–1960), the study situates Tullab al-Nur, a global community of learners, within the broader framework of tawhidic epistemology, where knowledge (‘ilm) is spiritually rooted, ethically directed, and communally embodied. Through a qualitative and reflective analysis, the paper identifies three key mechanisms by which darshane nurtures identity: (1) the internalization of metaphysical principles such as tawhid, hikmah, and hizmet; (2) dialogical learning (sohbet) that connects classical Islamic texts to modern dilemmas; and (3) the adaptive use of digital platforms without abandoning sacred pedagogical values. The article argues that darshane transcends conventional models of Islamic education by integrating intellectual inquiry, spiritual refinement (tazkiyah), and public service into a coherent educational philosophy. In addition, it critically works with the modern. critiques which denounce the movement as either liberal or outmoded, and which claim that its epistemological faith makes it possible to synthesize creatively and not to take sides. The research comes to the conclusion that the concept of darshane provides a repeatable example of the Islamic educational model. intelligent, neurotically sound, and spiritually oriented–based on. tradition but sensitive to world realities. Practical implications provide the necessity of shared structures between educators, technologists and civil society participants to maintain. this integrative model both formally and informally.